(untitled) (JED (Jurnal Etika Demokrasi), 2020)
Abstract. This study aims to explore the efforts of civic virtue coaching in elementary schools. The research method used is descriptive qualitative — retrieval of data through observation, interviews, and documentation. Data analysis uses the Miles and Huberman model. The subjects of the study were the first-grade students of SD N 4 Darmakradenan, Ajibarang, Banyumas, Indonesia, 2019/2020 academic year. The results showed that the development of Civic Virtue in Elementary Schools at SD N 4 Darmakradenan Ajibrarabang Banyumas was formulated by instilling Civic Virtue concepts on a scale of concept recognition about nationality to foster a sense of love for the motherland. Besides, the findings also confirm that Pancasila Education and Citizenship (PPKn) in Elementary Schools serve as a bridge in the efforts to foster Civic Virtue in Primary Schools 4 N Darmakradenan, Ajibarang, Banyumas. Further research on the opportunity to encourage Civic Virtue in Primary Schools is recommended in a new study in this article Keywords: Civic Virtue, Elementary School, Coaching. Abstrak. Penelitian ini bertujuan untuk mengeksplorasi usaha pembinaan civic virtue di Sekolah Dasar. Metode penleitian yang digunakan adalah kualitatif deskriptif. Pengambilan data melalui observasi, wawancara, dan dokumentasi. Analisi data menggunakan model Miles dan Huberman. Subjek penelitian adalah siswa siswi kelas 1 SD N 4 Darmakradenan, Ajibarang, Banyumas,Indonesia,Tahun ajaran 2019/2020. Hasil penelitian menunjukkan bahwa pembinaan Civic Virtue di Sekolah Dasar di SD N 4 Darmakradenan Ajibrarabang Banyumas di formulasikan dengan menanamkan konsep-konsep Civic Virtue dalam skala pengenalan konsep tentang kebangsaan sehingga dapat menumbuhkan rasa cinta tanah air. Selain itu, hasil temuan juga menegaskan bahwa Pendidikan Pancasila dan Kewarganegaan (PPKn) di Sekolah Dasar menjadi jembatan dalam upaya pembinaan Civic Virtue di Sekolah Dasar SD N 4 Darmakradenan, Ajibarang, Banyumas. Penelitian lebih lanjut tentang peluang pembinaan Civic Virtue di Sekolah Dasar di anjurkan dalam penelitian selanjutnya dalam artikel ini. Kata Kunci: civic virtue, sekolah dasar, pembinaan.